1990
DOI: 10.1002/1097-0142(19900615)65:12<2811::aid-cncr2820651234>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Association of nonmelanoma skin cancer and actinic keratosis with cumulative solar ultraviolet exposure in Maryland watermen

Abstract: To establish the relationship between ultraviolet-B radiation and squamous cell carcinoma (SCC), basal cell carcinoma (BCC), and actinic keratosis (AK), a cross-sectional prevalence survey was performed in a sample of 808 white, male watermen 30 years of age and older residing in the Eastern Shore of Maryland. A measure of personal cumulative ultraviolet-B exposure was determined for each subject from data collected through interviews and field and laboratory measurements. A personal interview elicited skin ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
127
1
12

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(146 citation statements)
references
References 13 publications
6
127
1
12
Order By: Relevance
“…A positive association between sunlight exposure and skin cancer has been reported previously (Viyasa et al, 1990;Green and Battistutta, 1990) (Tam et al, 1979). Methylation of arsenic is considerd to be a detoxication mechanism because DMA has a low acute toxicity (Vahter and Marafante, 1983) and is rapidly excreted in the urine (Vahter et al, 1984).…”
Section: Diagnosis Ofskin Cancermentioning
confidence: 99%
“…A positive association between sunlight exposure and skin cancer has been reported previously (Viyasa et al, 1990;Green and Battistutta, 1990) (Tam et al, 1979). Methylation of arsenic is considerd to be a detoxication mechanism because DMA has a low acute toxicity (Vahter and Marafante, 1983) and is rapidly excreted in the urine (Vahter et al, 1984).…”
Section: Diagnosis Ofskin Cancermentioning
confidence: 99%
“…In addition, report of exposure to the sun does not necessarily capture the relevant dose at a cellular level due to differences in skin type. There are several markers of chronic sun exposure, including actinic keratosis (24), elastosis, telangiectasia, and solar lentigines (25)(26)(27)(28) and assessment of the association between these and BCC provides a more objective measure of the impact of cumulative UVR exposure. Although there are studies that have explored this issue, there has been no previous attempt to synthesize this literature.…”
Section: Introductionmentioning
confidence: 99%
“…An early study of watermen from the eastern shore of Maryland found that average annual exposure to ambient UVB radiation was strongly correlated with the prevalence of SCC, whereas BCC did not have such a correlation (8), especially in watermen younger than 60 years of age (9). Because of the association between defects in DNA repair genes (10) and the poor DNA repair phenotype (11) that causes a high incidence of BCC and SCC in xeroderma pigmentosum (XP) patients (12), this watermen study provided much enthusiasm for further studying the DNA repair capacity (DRC) as a marker for genetic susceptibility to NMSC in the general population.…”
mentioning
confidence: 99%